Medical Errors and Patient Safety as Perceived by Nurses (The Review of Diabetic Studies, 2024)
A worldwide issue, patient safety is a crucial component of the caliber of health care systems. One of the main risk factors for medical mistakes that compromise patient safety is the human element. In order to investigate how this element affects patient safety in the hospitals in the Saudi Arabian city of Ha'il, nurses' views of the categories of respondents' characteristics in relation to risk factors were evaluated using the ANVOA (One Way). At P